KONFLIK BATIN TOKOH UTAMA DALAM NOVEL KARYA RUWI MEITA TINJAUAN PSIKOLOGI SASTRA DAN RELEVANSINYA SEBAGAI BAHAN AJAR SASTRA INDONESIA DI SMA - Silmi Nur Azizah Tara; Muhammad Rohmadi; Kundharu Saddhono (Universitas Sebelas Maret, 2019)
The purpose of this study was to describe: the form of ego defense mechanism used by the main character in resolving inner conflicts, character education values, and relevance as literary learning material in high school. This research was carried out with qualitative descriptive method and using literary psychology approach. The results of this study indicate that: 1) the form of inner conflict in the Kaliluna novel: Luka di Salamanca by Ruwi Meita includes the conflict away and the conflict approaching; (2) the form of the ego defense mechanism used by Kaliluna to resolve inner conflicts experienced by the main character in the novel Kaliluna: Luka di Salamanca in the form of sublimation, diversion, aggression, projection, reaction formation, apathy, and fantasy; (3) the values of character education contained in the novel include religious, tolerance, discipline, hard work, creative, independent, curiosity, national spirit, friendly / communicative, fond of reading, social care, and responsibility; (4) Kaliluna : Luka di Salamanca is relevant to teaching materials for learning Indonesian literature in high school because it is in accordance with the principles of good teaching materials and provides many positive values to be realized in daily life